A detailed statistical study of heterogeneous, homogeneous and nucleation models for dissolution of waste concrete sample for mineral carbonation. (1st September 2018) - Irfan, Muhammad Faisal; Usman, Muhammad Rashid; Rashid, Ajaz
Abstract: One of the key issues associated to mineral carbonation is the slow kinetic rate of leaching process. Hence it is highly important to study the kinetics of the leaching process in detail. This paper deals with the detailed analytical and statistical studies of calcium leaching from waste concrete sample. For comparison, another potential waste i.e. CKD was also selected. Different analytical approaches such as ICP, EDS, XRD, and SEM were used. Based on the preliminary results, at the experimental conditions of 2 M solution of each ligand for 2 h at 70 °C, HNO3 was found to be more proficient as compared to the rest of ligands (propionic acid, NH4 Cl, and NaOH) used. In addition, detailed kinetic study was also performed for different temperatures and HNO3 concentrations. Different heterogeneous (M1-M9), homogeneous (M10, M11), and nucleation i.e. JMAEK (M12) models were implemented to represent the experimental data. Statistical tools such as SSE, SEE, R 2, F-value, and t-values of the regression parameters were used to discriminate various kinetic models and among them, nucleation model (M12) was found best to describe the experimental data. A low activation energy (25 kJ/mol) indicates that diffusion could be the rate controlling step for the dissolution of waste concrete sample. Highlights: Analytical and statistical study of waste samples dissolution for Ca leaching is presented. Supernatants and precipitates are analyzed by ICP, SEM, EDS, and XRD techniques. HNO3 is found to be the best ligand among the various ligands tested. Twelve different homogeneous, heterogeneous and nucleation models are tested. Based on the rigorous statistical tools, the results are best represented by Avrami model.